2020
DOI: 10.3390/ijms21155425
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of LMX1A Contributes to Cancer Progression in Lung Cancer Cells

Abstract: Epigenetic modification is considered a major mechanism of the inactivation of tumor suppressor genes that finally contributes to carcinogenesis. LIM homeobox transcription factor 1α (LMX1A) is one of the LIM-homeobox-containing genes that is a critical regulator of growth and differentiation. Recently, LMX1A was shown to be hypermethylated and functioned as a tumor suppressor in cervical cancer, ovarian cancer, and gastric cancer. However, its role in lung cancer has not yet been clarified. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Fibrillin-1 ( FBN1 ), encoding an extracellular matrix glycoprotein that serves as a structural component of calcium-binding microfibrils, seems to play an important role in tumor-related immune infiltration and has been proposed as a prognostic and predictive biomarker for immune therapy against pancreatic ductal adenocarcinoma (PDAC) ( Luan et al, 2020 ). Finally, colony stimulating factor 2 receptor subunit beta (CSF2RB) has been shown to regulate epithelial-mesenchymal transition (EMT) in human lung cancer cells ( Wu et al, 2020 ; Rudisch et al, 2015 ). Our study also shows mutations in genes that are involved in mechanisms relevant in cell-cell adhesion, microtubule activity or extracellular matrix conformation, thereby indicating the presence of commonly altered functions in LUSC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillin-1 ( FBN1 ), encoding an extracellular matrix glycoprotein that serves as a structural component of calcium-binding microfibrils, seems to play an important role in tumor-related immune infiltration and has been proposed as a prognostic and predictive biomarker for immune therapy against pancreatic ductal adenocarcinoma (PDAC) ( Luan et al, 2020 ). Finally, colony stimulating factor 2 receptor subunit beta (CSF2RB) has been shown to regulate epithelial-mesenchymal transition (EMT) in human lung cancer cells ( Wu et al, 2020 ; Rudisch et al, 2015 ). Our study also shows mutations in genes that are involved in mechanisms relevant in cell-cell adhesion, microtubule activity or extracellular matrix conformation, thereby indicating the presence of commonly altered functions in LUSC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several protein-encoding genes have been identified as targets regulated by DNA methylation, such as ALDH2, LMX1A, and SLC22A18. [9][10][11] The hypermethylation or hypomethylation causes downregulation or overexpression of target genes, which further regulate NSCLC tumorigenesis and progression. 12 Apart from protein-encoding genes, several non-coding RNAs were also identified to be targets of DNA methylation, such as miR-21 and miR-196b.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Several protein-encoding genes have been identified as targets regulated by DNA methylation, such as ALDH2 , LMX1A , and SLC22A18 . 9 , 10 , 11 The hypermethylation or hypomethylation causes downregulation or overexpression of target genes, which further regulate NSCLC tumorigenesis and progression. 12 …”
Section: Introductionmentioning
confidence: 99%
“…e Oncomine database (https:// www.oncomine.org/) [11] and the Kaplan-Meier Plotter (https://kmplot.com/analysis/) [20] was used to determine the effect of differentially expressed genes (DEGs) under different concentrations of oxygen on the overall survival of NSCLC patients. e survival curve was downloaded from the following data links: TCGA CAARRAY GSE31210, GSE14814, GSE19188, GSE29013, GSE30219, GSE3141, GSE31908, GSE37745, GSE43580, GSE4573, GSE50081, GSE31908, and GSE8894.…”
Section: Survival Analysismentioning
confidence: 99%
“…e concept of tumor hypoxia was first presented in 1955, while studying tumor specimens obtained from lung cancer patients [6]. Over the next 60 years, scientists have gradually confirmed that hypoxia is a widespread characteristic in tumors and is closely related to tumor differentiation, angiogenesis, energy metabolism, invasion, and drug resistance [7][8][9][10][11]. Compared with normal cells, cancer cells are more adapted to grow in anoxic environments [12].…”
Section: Introductionmentioning
confidence: 99%